Identification of the adhesive domain of AtaA from Acinetobacter sp. Tol 5 and its application in immobilizing Escherichia coli - Yoshimoto, Shogo; Aoki, Sota; Ohara, Yuki; Ishikawa, Masahito; Suzuki, Atsuo; Linke, Dirk; Lupas, Andrei N.; Hori, Katsutoshi (Frontiers in Bioengineering and Biotechnology, 2023)
Cell immobilization is an important technique for efficiently utilizing whole-cell biocatalysts. We previously invented a method for bacterial cell immobilization using AtaA, a trimeric autotransporter adhesin from the highly sticky bacterium Acinetobacter sp. Tol 5. However, except for Acinetobacter species, only one bacterium has been successfully immobilized using AtaA. This is probably because the heterologous expression of large AtaA (1MDa), that is a homotrimer of polypeptide chains composed of 3,630 amino acids, is difficult. In this study, we identified the adhesive domain of AtaA and constructed a miniaturized AtaA (mini-AtaA) to improve the heterologous expression of ataA. In-frame deletion mutants were used to perform functional mapping, revealing that the N-terminal head domain is essential for the adhesive feature of AtaA. The mini-AtaA, which contains a homotrimer of polypeptide chains from 775 amino acids and lacks the unnecessary part for its adhesion, was properly expressed in E. coli, and a larger amount of molecules was displayed on the cell surface than that of full-length AtaA (FL-AtaA). The immobilization ratio of E. coli cells expressing mini-AtaA on a polyurethane foam support was significantly higher compared to the cells with or without FL-AtaA expression, respectively. The expression of mini-AtaA in E. coli had little effect on the cell growth and the activity of another enzyme reflecting the production level, and the immobilized E. coli cells could be used for repetitive enzymatic reactions as a whole-cell catalyst.